Pemanfaatan Daun Kratom sebagai Alternatif Pengobatan Penyakit Gangguan Kecemasan dan Depresi - Hafidzah, Nur Hidayatul; Rizki, Andini Sri; Feki, Muhammad; Maizuldri, Zaky; Sujatmiati, Arti (PT Hakhara Akademia Indonesia, 2024)
This research aims to use kratom leaves as an alternative treatment for anxiety disorders and depression. The writing method used in this scientific paper is using qualitative methods. The findings of this research are that Kratom leaves contain the alkaloid compounds Mitragynine and 7-Hydroxymitragynine, Spsiocilliatin, Spesioginin, Painantein which can be used by the community as a traditional medicine to treat diarrhea, fatigue, muscle aches, coughs, increase body endurance, reduce high blood pressure, increases energy, overcomes depression and anxiety disorders, anti-diabetic, and sexual stimulant but in the right dose. The stages of processing kratom leaves into medicine for anxiety and depression disorders consist of planting kratom leaves, picking kratom leaves, withering kratom leaves, grinding kratom leaves, oxidizing kratom leaves, drying kratom leaves, and packaging. How to use the medicinal concoction of kratom leaves by mixing the kratom leaf powder with cold or hot water, then stirring until smooth, and drinking in one gulp.